EFEKTIVITAS PENANGANAN KASUS KEKERASAN TERHADAP PEREMPUAN DAN ANAK OLEH DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KOTA SORONG - Rahmi, Aulia; Kitaby A., Magfirah Ummul (Muadalah : Jurnal Hukum, 2023)
Violence is an act or threat to oneself, a group of people or society or individuals that causes death, loss, psychology, trauma or deprivation of rights. Cases of violence against women and children are nothing new. There is a lot of violence against women and children that often happens around us. Cases of violence against women and children are increasing every year. The change of Sorong City to become the Capital City of Southwest Papua Province had a major influence on cases of violence against women and children in Sorong City, with an increase in population, the number of cases of violence also increased. Cases of violence against women and children come in various forms of violence. Ranging from physical and psychological violence, domestic violence, neglect, harassment to trafficking in persons. Cases of violence against women and children may occur in the social environment, including the family environment, the workplace, to educational institutions.